Investigation of Thickened Supercritical Carbon Dioxide for Waterless Fracturing of Shale Formation - MUHAMMED RASHIK MOJID, MUHAMMED RASHIK MOJID (2021)
Much attention is given to supercritical carbon dioxide (Sc-CO2) as a fracturing fluid for hydrocarbon recovery from shale. However, poor proppant carrying capacity, high frictional resistance, large displacement, and sand plugging have limited its application. This research aims to investigate the thickening of Sc-CO2 by using viscoelastic surfactants (VES) for increasing Sc-CO2’s proppant carrying capacity using molecular simulation. It also stimulates the preferential adsorption of thickened Sc-CO2 over methane (CH4) to investigate potential sequestration. Shale samples from Eagle Ford, Mancos, and Wolfcamp formations are characterized by using field emission scanning electron microscope, surface area analyzer and porosimetry system, X-ray diffraction, helium porosimeter, and total carbon analyzer. The density, surface area, and volume of the shale samples range from 2.06 - 2.67 g/cm3, 368.8871 - 540.2255 m2/g, and 0.3515 - 0.4914 cm3/g, respectively. These results are used to validate a heterogeneous shale model which was developed to carry out adsorption simulation studies. A molecular simulation study on the thickening of Sc-CO2 was carried out at temperatures and pressures ranging from 298 K to 305 K and from 100 kPa to 7400 kPa, respectively. Fluorinated VES, N-ethyl perfluorooctyl sulfonamide (N-ETFOSA), and non-fluorinated VES, N,N,N'-Trimethyl-1,3-propanediamine (N,N,N'-TM-1,3-PDA) were used as thickening agents. As a result, N,N,N'-TM-1,3-PDA shows better solubility in Sc-CO2 than N-ETFOSA. However, N,N,N'-TM-1,3-PDA increases the viscosity of Sc-CO2 by 36 times while N-ETFOSA increases the viscosity of Sc-CO2 by 156 times. Moreover, the adsorption study has shown that the selectivity of N-ETFOSA thickened Sc-CO2 at higher pressure and temperature is better than methane and N,N,N'-TM-1,3-PDA thickened Sc-CO2 as well. In addition, both thickening and adsorption simulation results were validated using literature data. In conclusion, the results indicate that thickened Sc-CO2 has the potential to become a viable alternative to the conventional water-based fracturing fluid.